Fabrication of high-quality GaAs-based photodetector arrays on Si - Kim, SangHyeon; Geum, Dae-Myeong; Park, Min-Su; Kim, Ho-Sung; Song, Jin Dong; Choi, Won Jun (AMER INST PHYSICS, 2017)
We report on fabrication and characterization of high-quality 32 x 32 GaAs photodetector (PD) arrays on Si substrates fabricated by wafer bonding and epitaxial lift-off (ELO) techniques. Fabricated GaAs PD arrays showed good crystal quality on Si substrates with Raman spectra and X-ray diffraction measurement. Also, pitch scaling gave us faster ELO process time as well as high-density PD arrays. Furthermore, we investigated electrical and optical characteristics of fabricated GaAs pin PD arrays on Si substrates. Especially, the components of dark current characteristics were also evaluated, because it is very important to explore further pitch scaling. Published by AIP Publishing.
Keywords: EPITAXIAL LIFT-OFF; WELL INFRARED PHOTODETECTORS; PHOTODIODE; BANDWIDTH; WAFER; SUBSTRATE